Considerations for Universal Mental Health Screening in Schools: A Qualitative Study of Implementation Determinants. - Kidd, Jessica; Williams Splett, Joni; Lord, Reilly; Varner, Mia; Yost, Michayla; Corbin, Cathy; Sonsteng-Person, Melanie (Journal of Emotional & Behavioral Disorders, 2026)
Despite widespread recommendations to implement universal mental health screening (UMHS), there remains an "implementation gap" between evidence-based practices and how these practices are routinely adopted and implemented in schools. Research with end-users in mind is needed to identify implementation barriers and facilitators for UMHS and inform feasible implementation strategies that ensure UMHS is used as intended in practice to reduce youths' unaddressed mental health risk. Guided by the Consolidated Framework for Implementation Research (CFIR), a qualitative study of practice-based evidence was conducted to examine the implementation determinants of UMHS within a tiered mental health system. Interviews with school leaders (n = 11) within Florida school districts implementing UMHS were analyzed using thematic analysis. Results identify how the outer, inner, individual, program, and process-level determinants affect the implementation of screening. Specifically, buy-in was considered the most significant direct and indirect factor that influenced implementation within all levels of the CFIR framework. Implementation strategies connected to the determinants identified in this study are discussed, along with recommendations for future research to improve the implementation of UMHS.